Structural aging and degradation of human fingernail plates upon cosmetic agents - S. Kulesza; M. Bramowicz; M. Gwoździk; S. Wilczyński; A.M. Goździejewska (Archives of Metallurgy and Materials, 2019)
The knowledge whether and how chemical species react with tissues is important because of protection against harmful factors, diagnose of dermatological diseases, validation of dermatological procedures as well as effectiveness of topical therapies. In presented work the effects of chemical agents on plates of human fingernails were studied using Atomic Force Microscopy and Scanning Electron Microscopy. Apart from that, mapping of the elastic properties of the nails was also carried out. To obtain reliable measures of spatial evolution of the surface variations, recorded images were analyzed in terms of scaling invariance brought by fractal geometry, instead of common though not unique statistical measures.